2018
DOI: 10.1192/bjb.2018.28
|View full text |Cite
|
Sign up to set email alerts
|

The over-35s: early intervention in psychosis services entering uncharted territory

Abstract: Aims and methodFollowing the introduction of new standards for early intervention in psychosis (EIP) in England, EIP services are accepting referrals for people aged 35–65. The Cambridgeshire and Peterborough EIP service (CAMEO) aimed to explore the immediate implications for the service, especially with regards to referral numbers and sources. Data were collected from April 2016 to June 2017.ResultsReferrals for over-35s represented 25.7% of all new referrals. Fifty per cent of referrals for over-35s were acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
(30 reference statements)
2
12
2
Order By: Relevance
“…The operational definition of first-episode psychosis may exclude potential clients based on the duration of psychotic symptoms, duration of antipsychotic medication, or prior help-seeking contacts (Breitborde et al ., 2009), and in the case of the EPI program in the current study, exclusions are also made if there is an affective presentation at first onset. Our findings suggest that only 40% of people identified by our case-finding algorithm who were screened by the EPI program were ultimately admitted, which is in line with reported estimates from some programs (O'Donoghue et al ., 2012; Clay et al ., 2018), but much lower than others (Kirkbride et al ., 2017). A recent study used electronic medical records to ‘confirm’ whether cases identified in health administrative data would meet the case definition for first-episode psychosis.…”
Section: Discussionmentioning
confidence: 54%
“…The operational definition of first-episode psychosis may exclude potential clients based on the duration of psychotic symptoms, duration of antipsychotic medication, or prior help-seeking contacts (Breitborde et al ., 2009), and in the case of the EPI program in the current study, exclusions are also made if there is an affective presentation at first onset. Our findings suggest that only 40% of people identified by our case-finding algorithm who were screened by the EPI program were ultimately admitted, which is in line with reported estimates from some programs (O'Donoghue et al ., 2012; Clay et al ., 2018), but much lower than others (Kirkbride et al ., 2017). A recent study used electronic medical records to ‘confirm’ whether cases identified in health administrative data would meet the case definition for first-episode psychosis.…”
Section: Discussionmentioning
confidence: 54%
“…Additional support should be given to patients aged 39-64 who are at greatest risk of dying by external causes v. their community-treated counterparts with SMIs. From 2016, EIP services were expanded to support patients aged over 35 years (Clay et al, 2018). Further research investigating the impact of widening the eligible age range for this service on risk of dying by external causes is needed.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that acute onset and presentation of psychosis may be a significant indicator for accessing specialist service. This is reflected in findings from recent studies, following the implementation of Access and Waiting Time standard, which suggest that patients aged > 35 years present with complex needs [ 58 , 59 ]. However, further research is needed to shed light on which factors influence pathways to care for patients over 35 years.…”
Section: Discussionmentioning
confidence: 99%